Pengaruh Disiplin Kerja, Profesionalisme Kerja, dan Lingkungan Kerja Fisik terhadap Kinerja Pegawai Pada Kantor Kementerian Agama Kabupaten Klungkung - Cahyani, Ida Ayu Bintang; Agustina, Made Dian Putri; Pratiwi, Komang Ary (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Enhancing staff productivity stands as the paramount task for management, given that the attainment of objectives and the enduring prosperity of the organization hinge upon the caliber of its workforce. This study aims to assess the factors impacting employee performance within the Office of the Ministry of Religious Affairs in the Klungkung Regency. The investigation involved 34 participants, selected using the total sampling method. Data collection was executed through questionnaire distribution. The analytical approach employed was multiple linear regression analysis, examining the influence of Work Discipline, Professionalism, and the physical work environment on employee performance within the Office of the Ministry of Religious Affairs in Klungkung Regency. The findings from hypothesis testing reveal that work discipline, professionalism, and the physical work environment significantly and positively affect employee performance within the Office of the Ministry of Religious Affairs in Klungkung Regency